Implementing Multimedia Teaching to Improve Students’ Motivation and Critical Thinking Skills Based on the Students’ Learning Styles at Mahatma Gading School - Usha Naraindas Bharwani (Jurnal Teropong Pendidikan, 2021)
This study investigated implementing multimedia teaching to improve students’ motivation and critical thinking skills based on students learning styles at Mahatma Gading School. Multimedia learning offers a significant opportunity to reach the greatest number of students and most effectively supports students with different learning styles. The study employed quantitative weak experimental of static group pre-test post-test. The respondents were 67 students from Mahatma Gading School academic year 2016. There was no control group. The data was computed using SPSS VERSION 22. Results of the pretest were observed before teaching and results of the posttest was conducted after teaching. Instruments used for data collection were in the form of test and questionnaire. The test was to measure students’ critical thinking skills and questionnaire to measure students learning styles and motivation. The researcher analyzed the data through Descriptive Statistics, and Wilcoxon Test. The data was then analyzed, which showed there was a statistically significant difference between students after implementing multimedia during the Science class. However, the result of the Wilcoxon Test on reading learners had no significant differences in students learning styles.